2021
DOI: 10.1101/2021.02.08.430362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A transferrable and integrative type I-F Cascade for heterologous genome editing and transcription modulation

Abstract: The Class 1 type I CRISPR-Cas systems represent the most abundant and diverse CRISPR systems in nature. However, their applications for generic genome editing have been hindered by difficulties of introducing the class-specific, multi-component effectors in heterologous hosts for functioning. Here we established a transferrable Cascade system that enables stable integration and expression of a complete and highly active I-F Cascade in the notoriously recalcitrant and diverse P. aeruginosa genomes by conjugatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…It was reported that very few survivors could be identified as escapers carrying mutations that impede the CRISPR-Cas function, such as deletion of the targeting spacer from the CRISPR array through recombination between identical repeats [41,42]. Very recently, Xu et al demonstrated that all the bacterial cells escaped from self-targeting by a Type I-F system carried mutations in the key components of the Cascade, and more importantly, they found that genome-targeting by the Type I-F system is more specific than that by a Type II Cas9 [43]. Also, as the nCas9 showed an obvious advantage in helping base editing over other Cas9 variants [8], we envision that nCas3-based toolkits, such as base editors, would be soon available for various bacteria harbouring an active Type I CRISRP-Cas.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that very few survivors could be identified as escapers carrying mutations that impede the CRISPR-Cas function, such as deletion of the targeting spacer from the CRISPR array through recombination between identical repeats [41,42]. Very recently, Xu et al demonstrated that all the bacterial cells escaped from self-targeting by a Type I-F system carried mutations in the key components of the Cascade, and more importantly, they found that genome-targeting by the Type I-F system is more specific than that by a Type II Cas9 [43]. Also, as the nCas9 showed an obvious advantage in helping base editing over other Cas9 variants [8], we envision that nCas3-based toolkits, such as base editors, would be soon available for various bacteria harbouring an active Type I CRISRP-Cas.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors mainly contribute to the emerged resistance against CRISPR-Cas antimicrobials in the escaped colonies, such as the spontaneous mutations in the Cas genes or the target sequences, spacer excision owing to the homologous recombination between the repeats, presence of the anti-CRISPR (Acr) genes in the target host genomes, and repressed expression/activity of cas proteins. In a recent study, when the genomes and mini-CRISPRs isolated from escaped colonies from CRISPR-Cas-mediated genome targeting were sequenced, either mutations in the cas genes or the excision of spacers were identified ( Xu et al, 2021a ). Thus, future efforts to reduce the emerged resistance against CRISPR-Cas antimicrobials should focus on preventing these spontaneous mutations in cas genes or crRNA-expressing elements, such as modifying the repeat sequences to prevent their homologous recombination ( Csörgő et al, 2020 ).…”
Section: Emerged Resistance Against Crispr-cas Antimicrobialsmentioning
confidence: 99%
“…Feasibility of the “anti-anti-CRISPR” strategy has been indicated in a model strain P. aeruginosa PAO1 which was lysogenized by a recombinant DMS3m phage expressing an anti-CRISPR gene acrIC1 ( Csörgő et al, 2020 ). However, its robustness in the clinically relevant strains is compromised and remains further improvement ( Xu et al, 2021a ).…”
Section: Emerged Resistance Against Crispr-cas Antimicrobialsmentioning
confidence: 99%
“…Our current knowledge about CRISPR-mediated genome editing in bacteria mainly come from a number of human pathogens as well as industrial and laboratory strains, such as Escherichia coli [8][9][10], Pseudomonas [11,12], Mycobacterium [13],…”
Section: Introductionmentioning
confidence: 99%